Hepatitis C – Knowledge and Attitude Among Patients Attending OPDs in Tertiary Care Hospital in Karachi: A Patient’s Survey (Medical Forum Monthly, 2022)
Objective: To assess knowledge and attitude about Hepatitis C among Patients attending tertiary care hospital at Gadap town, Malir Karachi.Study Design: Cross Sectional StudyPlace and Duration of Study: This study was conducted at the Al-Tibri Medical College, Isra university campus at Gadap town, Malir Karachi. Survey was conducted from October 2018 to March 2019.Materials and Methods: Systematic (Random) Sampling Technique was used. Data was collected by help of a pre-tested semi-structured questionnaire. Data was analyzed by using SPSS version -24.Results: A total of 259 patients filled/answered the questionnaire, waiting outside of general OPDs to see a doctor. (n=259) Total number of male Patients were n=101 (39%) and females n=158 (61%). The results findings revealed that Out of the 259 participants, 92 (35.5%) showed adequate and satisfied level of knowledge about Hepatitis C. whereas, 167 (64.5%) of the study participants possessed ‘in-adequate and poor knowledge’ regarding Hepatitis C. Majority (93.4%) of survey participants was not aware of good practice against Hepatitis C and 88.1% of the participants were inadequate knowledge about utilization of healthcare services regarding hepatitis C.Conclusion: There was a prominent lack of awareness with respect to the HCV infection, its risk factors and prevention among the Gadap town community in Malir Karachi.